Implementation of "Morals" in Cultural Values and Organizational Behavior: Interventions for Reducing and Aligning Cultural Values in BUMN - Prastowo, Helsa Evania; Suhariadi, Fendy (Psikostudia : Jurnal Psikologi, 2023)
Organizational sustainability predicted by the implementation of cultural values which operationalized in work behavior. To improve sustainable performance, core value “AKHLAK” was created as the identity of all BUMN institutions. PT. X as part of BUMN, must adjust with those values by aligning their values. The purpose of this study is to develop an intervention for cascading-aligning PT. X's cultural values with AKHLAK and preparing work behavior’s guidelines which will be used as behavior-based performance appraisal. This study refers to a research & development method (Sugiyono, 2010) for testing the effectiveness of the intervention design. Research subjects are employees in the HR department and corporate culture. Data collection methods use document analysis and interviews. Data analysis was carried out by validating the intervention design with a subject matter expert. The results of the research show that there are some values that are deleted, but new values are also raised as a form of adjustment. The intervention was declared accepted by the user. Keberlangsungan organisasi diprediksi dari implementasi nilai budaya dalam perilaku kerja anggotanya. Dalam rangka peningkatan kinerja berkelanjutan, Kementerian BUMN mencetuskan core value AKHLAK sebagai identitas dan perekat budaya kerja bersama. Penyesuaian nilai budaya dengan menyelaraskan nilai budaya khas yang dimiliki tiap organisasi perlu dilakukan. Tujuan penelitian adalah menyusun intervensi penurunan dan penyelarasan nilai budaya PT.X dengan core value AKHLAK termasuk penyusunan panduan perilaku  sebagai dasar penilaian kinerja berbasis perilaku. Penelitian ini menggunakan metode research & development sebagai dasar pengujian efektivitas rancangan intervensi. Subjek penelitian adalah karyawan jabatan struktural departemen SDM dan corporate culture. Metode pengumpulan data berupa analisis dokumen dan wawancara. Analisis data dilakukan dengan memvalidasi desain intervensi ada subject matter expert. Hasil penelitian menunjukkan bahwa terdapat beberapa nilai yang dihapuskan, namun juga nilai baru dimunculkan sebagai bentuk penyesuaian. Intervensi yang dilakukan dinyatakan diterima oleh user.